The Role of Classroom Management in Improving the Academic Achievement of Students - Lasmi, Hardiyanti; Herlina, Besse; Basir, Sutrisman; Kurnia, Kurnia; Fina, Fina; Nurfadilla, Nurfadilla; Monang, Muhammad Asrul; Indah, Indah (Newinera Publisher, 2024)
It has come out clearly that classroom management is a critical component in determining the academic performance of students in classroom, however, the effectiveness of the aspects of management, namely, planning, organizing, directing and controlling depends on an ability to balance the same. In this research, the writer aims to discover how those functions enhance the students’ performance in Madrasah Tsanawiyah Private As’adiyah No. 2, an Indonesian religious school with both secular and religious components. This study employed a qualitative descriptive design to elicit data that explored the effects of classroom management on academics: Observations, interviews and document reviews were used. The identified strategies show that adaptive planning, systematic classroom arrangement, appropriate proportions of teacher intervention, and proper but variable monitorage promote both academic and personal development. Besides, the study informs contextual factors such as parental support, resources, and teacher stressful conditions that may impact successful management of the classroom. As such this study builds on the current knowledge in the classroom management literature by applying the strategies in the context of a madrasah that is a religious and diverse learning institution. Projected onto educators and policymakers the implications delineate the centrality of a contingency approach to class organization that is neither rigid nor lax but orders the environment in a way that complements the learning-teaching process and the students’ psychosocial character.